Development and distribution of submarine channels associated with sediment gravity flows in the modern Huanghe (Yellow River) subaqueous delta - An, Shikang; Feng, Aiping; Feng, Wei; Wang, Ya Ping; Chen, Yufeng; Wu, Zhuoyi; Chen, Xiaolong; Yu, Yonggui; Pan, Yupeng; Liu, Shihao (Frontiers in Marine Science, 2024)
Background Gravity-driven depositional processes play a pivotal role in shaping the geomorphology of subaqueous deltas worldwide, particularly by eroding the seafloor, leading to the formation of rugged submarine channels (SCs) and triggering various subaqueous geohazards. A comprehensive understanding of SCs is crucial for elucidating these depositional mechanisms and mitigating the risks associated with submarine geohazards. Although SCs in the Huanghe delta front have been previously identified, often described as seafloor gullies or subsurface “disturbed strata,” most studies have primarily concentrated on their engineering geological properties. However, there has been limited research on the scale, morphology, and development of these SCs, especially those that are buried within the stratigraphy. Methods This study integrates high-resolution sub-bottom data, sediment core analyses, and historical bathymetric data to investigate the morphology, distribution, and formation mechanisms of SCs in the Huanghe subaqueous delta. Results The SCs, both buried and exposed, are widespread along the middle and upper delta front, predominantly located at or near the landward flank of sediment gravity flow (SGF) -related accumulations. The buried SCs are characterized by cut-and-fill structures with transparent to semi-transparent fills, indicating rapid infilling processes as SGF energy dissipates. These buried channels were preserved within different sets of delta front deposits formed during 1855–1964 CE, 1964–1976 CE, and 1976–2007 CE, with the latter two periods separated by a significant lobe-switching event in 1976 CE. This event, combined with prevailing southeastward sediment transport and erosional regimes, appears to have controlled the preservation of SCs along the delta front: SCs in the Diaokou Lobe's delta front (pre-1976) suffered significant erosion, leaving only one set of channel (erosional remnants) preserved, while the SCs in the Qingshuigou Lobe's delta front (post-1976) are characterized by well-preserved, multi-phase channels at different horizons. The cross-section morphology of the SCs reveal three primary types: symmetrical, asymmetrical, and composite, corresponding respectively to (1) idealized SGF incision, (2) uneven incision intensity on either side of the SCs, and (3) the merging of two or more symmetrical/asymmetrical SCs. Conclusions We describe in detail the morphology, distribution and development of SCs in the modern Huanghe subaqueous delta. These findings provide insights into the formation and distribution of SCs in other shallow marine settings, particularly in delta front areas, and potentially offer information for disaster prevention and engineering development in such regions.